PRESENTEEISM AMONG ELEMENTARY SCHOOL TEACHER: THE ROLE OF PRINCIPAL SUPPORT - Nugraini Aprilia; Intan Putri Maghfiroh; Sri Wahyuni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the effect of perceived supervisor support with the frequency of presenteeism based on gender and age in elementary school teachers in Gantung District, East Belitung Regency. The population of this study was 168 elementary school teachers, while the determination of the number of samples was obtained from the determination of the number of Isaac & Michael sample tables at a significance level of 5% so that a minimum sample of 114 teachers was obtained. The sampling method was a combination of convenience sampling and quota sampling techniques. The instruments used in this study were 6 items sub-scale perceived supervisor support developed from the Survey of Organizational Support (SPOS) (Eisenberger et al., 2001; Putri, 2007) and 1 item presenteeism’ frequency (Aronsson, et al., 2000). Based on the results of statistical data processing and analysis, it was known that the level of supervisors' support was in the high category with a percentage of 84%, while the frequency of presenteeism was in the low category with a percentage of 54%. Based on the results of hypothesis testing, it was known that the influence between perceived supervisor support on the frequency of presenteeism was only significant in elementary school teachers in middle adulthood (B = -. 019; t = -3.111; Sig = <. 05; R2 = 11.8%), especially the female teachers (B = - 023; t = -2.734; Sig = <. 05; R2 = 17.6%). The role of the principal in initiating, implementing and promoting a supportive climate in the school environment can be maximized as a form of support from superiors that is useful in intervening in presenteeism